Sacrospinous colpopexy versus McCall’s culdoplasty during vaginal hysterectomy in stage 3 and 4 prolapse for prevention of vault prolapse - Gulati, S. S.; Gupta, Samta; Khan, Neha; Agarwal, Shelly; Afreen, Naima; Ranjan, Megha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Pelvic organ prolapse is a common condition seen in women due to weakening of support of pelvic organs. Different surgical procedures have been adopted for suspension of vaginal vault during vaginal hysterectomy to restore vault to near normal anatomic position as preventive measures for vault prolapse. The aim of study was to compare the efficacy of the McCall’s culdoplasty and sacrospinous ligament colpopexy in stage 3 and 4 prolapse (POP-Q). Methods: This prospective study comprised 100 women presenting with stage 3 and 4 prolapse (POP-Q). They were divided into two equal groups of 50 each. The patients were randomized to undergo McCall’s culdoplasty (Group A) or sacrospinous ligament fixation (Group B) with vaginal hysterectomy based on note contained in an envelope comparative analysis was done, and patients were evaluated for intra-operative difficulties and immediate (48 hours) post-operative complications using SPSS-version 23 for statistical analysis. The patients were followed up at one month and one year to evaluate symptomatically and objectively. Results: In group A, patients with 3-degree prolapse 1 woman had hemorrhage and 1 woman had bladder injury intraoperatively. Whereas in group B, 5 women had hemorrhage and 1 woman had rectal injury intraoperatively. All complications were dealt successfully. No other major intra- and post-operative complications occurred. Conclusions: Vaginal hysterectomy with sacrospinous colpopexy resulted in better outcomes after surgery. Hence, it was concluded that unilateral or bilateral SSLF may be added to vaginal hysterectomy in patients of stage 3 or 4 prolapse.